Microtubule inhibition as a proposed mechanism for the anthelmintic effect of phytochemicals isolated from Cicerbita alpina - Mark James Horgan; Ines Sigg; Ioanna Poulopoulou; Francisco J. Rodriguez-Mejias; Eva Albertini; Pietro Fusani; Florian Fischer; Eftychia Martinidou; Daniela Schuster; Stefan Martens; Pidder Jansen Dürr; Matthias Gauly; et al. (Scientific Reports)
Abstract The alpine plant Cicerbita alpina (L.) Wallr., when grown as a sprout, is known as a bitter-tasting culinary delicacy. Recently it has also been reported to have anthelmintic activity, prompting further investigation into its mechanism of action. Liquid–liquid fractions were prepared from a methanolic extract of the aerial parts and were submitted in parallel to embryo development (ED), worm motility (WMT), and cytotoxicity assays for anthelmintic and toxicity evaluations. The anthelminthic assays revealed the more polar fractions to be most active against Ascaridia galli embryos (BuOH | 68% ED | c = 500 µg/ml and EtOAc | 65% ED | c = 500 µg/ml) and Caenorhabditis elegans adult worms (BuOH | 49% WMT | c = 150 µg/ml and EtOAc | 74% WMT | c = 150 µg/ml) suggesting the fraction’s constituents possess dual anthelmintic activity against multiple life-cycle stages (i.e., eggs, worms) of helminths. Additionally, the BuOH fraction was non-cytotoxic to human cell-lines. Subsequent FCC and SEC derived subfractions were submitted to the anthelmintic assay workflow and the enriched subfractions B1 and E3.8, phytochemically assigned as 11-β,13-dihydrolactucin and luteolin, demonstrated bioactivity against the embryo phenotype (B1 | 58% ED | c = 1.8 µM and E3.8 | 46% ED | c = 1.7 µM) within range of the flubendazole control. Furthermore, luteolin was found to inhibit C. elegans egg hatching (luteolin | 65% EH | c = 10 µM | t = 10 h) within the range of the control albendazole. Both identified anthelmintic phytochemicals were found to affect tubulin polymerisation at a concentration of c = 50 µM. Together with in silico virtual screening studies, these results suggest microtubule stabilisation as a possible anthelmintic target and mechanism of action. This work effectively advocates the consideration of C. alpina extracts and fractions for the development of herbal therapeutics against parasitic helminths.